2022
DOI: 10.1016/j.rinp.2021.105156
|View full text |Cite
|
Sign up to set email alerts
|

Cluster structure of superconducting phase and the nature of peaks in the doping dependences of the London penetration depth in iron pnictides

Abstract: The mechanism of formation of dome-like phase diagrams and the features of magnetic field penetration in iron pnictides with hetero-and isovalent doping are considered within the framework of the previously proposed model, which assumes the local character of doping and the cluster structure of resulted superconducting phase. It is shown that the proposed model, despite its simplicity and neglect of the features of the electronic structure, makes it possible not only to accurately calculate the positions of su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 27 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…This approach, however, fails to agree with many experiments where spatial variations of local charge density and superconducting order parameter are observed in doped specimens [3][4][5][6]. What is more, many experiments demonstrate that doped carriers in both cuprates and ferropnictides are strictly localized in the nearest vicinity of the dopant [7][8][9][10][11].Previously, we proposed a unified mechanism of local iso-and heterovalent (hole and electron) doping, which is implemented in superconducting cuprates and ferropnictides [12,13].The proposed mechanism assumes the local nature of the transformation of their band structure under doping, which leads to the formation of inhomogeneous cluster structure of the superconducting phase [13], the parameters of which are determined by the concentration of the dopant and crystal structure of the undoped compound.We have shown that basing only on the knowledge of the crystal structure and type of dopant, it is possible: 1) to accurately determine the positions of superconducting domes in the…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…This approach, however, fails to agree with many experiments where spatial variations of local charge density and superconducting order parameter are observed in doped specimens [3][4][5][6]. What is more, many experiments demonstrate that doped carriers in both cuprates and ferropnictides are strictly localized in the nearest vicinity of the dopant [7][8][9][10][11].Previously, we proposed a unified mechanism of local iso-and heterovalent (hole and electron) doping, which is implemented in superconducting cuprates and ferropnictides [12,13].The proposed mechanism assumes the local nature of the transformation of their band structure under doping, which leads to the formation of inhomogeneous cluster structure of the superconducting phase [13], the parameters of which are determined by the concentration of the dopant and crystal structure of the undoped compound.We have shown that basing only on the knowledge of the crystal structure and type of dopant, it is possible: 1) to accurately determine the positions of superconducting domes in the…”
mentioning
confidence: 88%
“…Therefore, despite the close relationship between Ba(Fe1-xNix)2As2 and Ba(Fe1-xCox)2As2, the geometry of their trion complexes is significantly different (Fig. 2 e, f), which causes the difference in the phase diagrams [13].…”
Section: Heterovalent Doping and Trionic Complexesmentioning
confidence: 99%
See 3 more Smart Citations